2013
DOI: 10.1103/physreve.87.012505
|View full text |Cite
|
Sign up to set email alerts
|

Memory function of turbulent fluctuations in soft-mode turbulence

Abstract: Modal relaxation dynamics has been observed experimentally to clarify statistical-physical properties of softmode turbulence, the spatiotemporal chaos observed in homeotropically aligned nematic liquid crystals. We found a dual structure, dynamical crossover associated with violation of time-reversal invariance, the corresponding time scales satisfying a dynamical scaling law. To specify the origin of the dual structure, the memory function due to non-thermal fluctuations has been defined by a projection-opera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Furthermore, we have proved that the memory effect due to the turbulent fluctuations originates from the patch structure [29].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, we have proved that the memory effect due to the turbulent fluctuations originates from the patch structure [29].…”
Section: Introductionmentioning
confidence: 95%
“…Mori and Okamura have numerically and analytically discovered a dual structure in the KS equation [28]; the relaxation dynamics is dominated by the deterministic and stochastic orbits in the short-time and long-time region, respectively. We experimentally found the dual structure of the modal autocorrelation in SMT and have theoretically revealed the mechanisms of the dual structure [29]. It has been reported that the spatiotemporal disorder in SMT generates non-thermal fluctuations [12,30] by which a nonMarkovian (i.e., memory) effect is expected to play a significant role in the relaxation dynamics.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations